O uso de tecnologias móveis no setor bancário: o caso de mobile banking do Banrisul (Banco do Estado do Rio Grande do Sul) - Santos, Diógenes Bonfati dos (Universidade do Vale do Rio dos Sinos, 2010)
This study was conducted to analyze the case of adoption of mobile banking (mobile banking or m-banking) and the profile of customers who use this service on a bench in the Brazilian context, the Banco do Estado do Rio Grande do Sul (Banrisul). The survey was conducted through a single case study in Banrisul, in which there were interviews and secondary data analysis. We investigated the characteristics of 628 users of mobile banking bank researched, covering 7046 to access this service. The survey used as the main theoretical Theory of Diffusion of Innovation (TDI) of Rogers (2003). Through data analysis it was possible to identify the habits and characteristics related to the behavior of users of m-banking services. The user profile of m-banking Banrisul was found: in general is male, single, have college degrees, average age 33 years (ranging from 26 to 35 years), with monthly income between R $ 2,000.00 R $ 3,000.00 reais. The main services used are: current account statement (65.2%), current account balance (30.4%) and transfers between accounts (2.6%), totaling 98.2% of services used during the study period. Knowledge of these data is important, because users were analyzed can be considered as innovative users or early adopters according to TDI. Knowing your profile and habits of access is useful for planning future actions related to the diffusion of mobile banking in this institution. The knowledge of the case is also useful to other institutions and researchers interested in mobile banking practices.
Keywords: Serviços bancários móveis; Mobile banking; M-banking; Banrisul; Instituições financeiras; Teoria da Difusão de Inovações; Perfil de usuários; Financial institutions; Theory of Diffusion of Innovations; Profile of users; ACCNPQ::Ciências Sociais Aplicadas::Administração